Đặt \(4-x=a\) và \(x-2=b\) \(\Rightarrow a+b=2\)
Ta có:
\(a^5+b^5=32\\\Leftrightarrow \left(a^3+b^3\right)\left(a^2+b^2\right)-a^2b^2\left(a+b\right)=32\\ \Leftrightarrow\left[\left(a+b\right)^3-3ab\left(a+b\right)\right]\left[\left(a+b\right)^2-2ab\right]-a^2b^2\left(a+b\right)=32\\\Leftrightarrow \left(8-6ab\right)\left(4-2ab\right)-2\left(ab\right)^2=32\\\Leftrightarrow 12\left(ab\right)^2-40ab+32=32\\\Leftrightarrow 4ab\left(3ab-10\right)=0\\\Leftrightarrow \left[{}\begin{matrix}4ab=0\\3ab-10=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}ab=0\\ab=\frac{10}{3}\end{matrix}\right.\)
Cho \(ab=\frac{10}{3}\) thì \(a,b\) là nghiệm của phương trình:
\(x^2-2x+\frac{10}{3}=0\) \(\Rightarrow\) Vô nghiệm
Cho \(ab=0\) thì \(a,b\) là nghiệm của phương trình:
\(x^2-2x=0\\\Leftrightarrow x\left(x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x-2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
\(\Rightarrow a=2vab=0\) hoặc \(a=0vab=2\)
Thử:
Với \(a=2vab=0\) ta có:
\(\Rightarrow4-x=2\\ \Leftrightarrow x=2\\ \Rightarrow x-2=0\\ \Leftrightarrow x=2\)
Vậy nghiệm của phương trình là \(2\)
Với \(a=0vab=2\) ta có:
\(\Rightarrow4-x=0\\ \Leftrightarrow x=4\\ \Rightarrow x-2=2\\\Leftrightarrow x=4\)
Vậy nghiệm của phương trình là 4
Do đó tập nghiệm của phương trình là: \(S=\left\{2;4\right\}\)